Usability Analysis of Inlislite Website in Elementary School Library in Penajam District using Heuristic Evaluation Method - Awalia, Andi Mentari; Hadisaputro, Elvin Leander; Wahyuni, Nuorma (Green Publisher Indonesia, 2022)
The purpose of this study was to see to what extent the quality of the system has functioned properly so that a system is able to achieve a certain goal so that the resulting output is effective, efficient, and achieves user satisfaction at the Elementary School Library in Penajam District Using the Heuristic Evaluation Method. The type of data used consists of primary data and secondary data. The research population includes all librarians from 40 schools, namely by distributing questionnaires to all elementary school librarian employees in the North Penajam Paser sub-district with a total of 90 people. The results showed that the level of Inlislite Website Usability Analysis actually had a positive and significant effect on users of the Elementary School Library Inslite website in Penajam District. In this case, the analysis of the test was carried out using the Cronbach Alpha's method with a total of 26 questionnaire items for the X variable and 5 for the Y variable with the Cronbach Alpha value 0.928 > 0.60 for the X variable and for the Y variable the Cronbach Alpha value was 0.617 > 0.60. it means that the questionnaire is reliable or consistent for use in influential research in Inlislite Website users at Elementary School Libraries.